Performance improvement of double-tube gas cooler in CO2 refrigeration system using nanofluids - Sarkar J. (My University, 2025)
The theoretical analyses of the double-tube gas cooler in transcritical carbon dioxide refrigeration cycle have been performed to study the performance improvement of gas cooler as well as CO2 cycle using Al2O3, TiO2, CuO, and Cu nanofluids as coolants. Effects of various operating parameters (nanofluid inlet temperature and mass flow rate, CO2 pressure and particle volume fraction) are studied as well. Use of nanofluid as coolant in double-tube gas cooler of CO2 cycle improves the gas cooler effectiveness, cooling capacity, and COP without penalty of pumping power. The CO2 cycle yields best performance using Al2O3-H2O as a coolant in double-tube gas cooler followed by TiO2-H2O, CuO-H2O, and Cu-H2O. The maximum cooling COP improvement of transcritical CO2 cycle for Al2O3-H2O is 25.4%, whereas that for TiO2-H2O is 23.8%, for CuOH2O - 20.2%, and for Cu-H2O - 16.2% for the given ranges of study. Study shows that the nanofluid may effectively use as coolant in double-tube gas cooler to improve the performance of transcritical CO2 refrigeration cycle.